Unlocking the potential exploring pharmacological properties from Apiaceae family - Kaldanay Kozhanova; Aigerim Alimanova; Ubaidilla Datkhayev; Elmira Serikbayeva; Farida Kayupova; Klara Zhumalina; Murat Ashirov; Kairat Zhakipbekov (Pharmacia)
The Apiaceae family, which encompasses a variety of economically important vegetables, herbs, and spices, stands out as one of the largest plant families. Crops such as anise, fennel, carrot, coriander, and parsley are not only valued for their culinary uses but also serve as important sources of botanical flavors and fragrances. Members of the Apiaceae family are known for their diverse medicinal properties, including antimicrobial and anti-inflammatory effects, as well as benefits for diabetes management and liver protection. In addition, these plants produce a number of unique, specialized metabolites such as volatile phenylpropanoids, furanocoumarins, sesquiterpene coumarins, polyacetylenes, and phthalides. Some of these compounds are rare phytochemicals found exclusively in this family, highlighting their potential for bioprospecting. The objective of this review is to support future research on Apiaceae by providing up-to-date information on their key characteristics, origin and traditional uses. It also collects and analyses the scattered information available in the literature on the chemical composition and biological activities of essential oils and various extracts from selected Apiaceae species, demonstrating their potential for pharmaceutical, cosmetic and other industrial applications.